International Procedural Means for the Suppression of Great Violations of International Humanitarian Law - Fekhar, Hicham (Journal of Legal Studies and Researches, 2020)
The study aims to establish procedures and mechanisms to ensure that perpetrators of grave violations of the rules of international humanitarian law are prosecuted. This is reflected in the measures that must be taken to address grave violations, whether they are related to mechanisms for international cooperation in this field, or the activation of the role of national and international criminal courts to confront such violations, suppress perpetrators and prevent impunity.